A Study on the Role of Buffers in Maintaining Acid-Base Balance in the Body - Farahmand, Mohammad Yosuf (Journal of Natural Sciences – Kabul University)
Acid-base balance is a complex physiological process that maintains a stable extracellular pH in the body. This balance is regulated by intracellular and extracellular buffers, as well as the respiratory and renal systems. The bicarbonate buffer system plays a fundamental role in this regulation. This article aims to review the normal physiological mechanisms involved in acid-base balance, the function of major buffer systems, and the contributions of the respiratory and urinary systems. Understanding these physiological processes is essential for managing and treating disorders caused by disruptions in acid-base homeostasis. This study is conducted as a review, and findings highlight those buffers and the respiratory system help minimize pH fluctuations, while full compensation occurs through renal adjustments.